Osteopontin activity modulates sex‐specific calcification in engineered valve tissue mimics - Megan E. Schroeder; Dilara Batan; Andrea Gonzalez Rodriguez; Kelly F. Speckl; Douglas K. Peters; Bruce E. Kirkpatrick; Grace K. Hach; Cierra J. Walker; Joseph C. Grim; Brian A. Aguado; Robert M. Weiss; Kristi S. Anseth (Bioengineering & Translational Medicine)
Abstract Patients with aortic valve stenosis (AVS) have sexually dimorphic phenotypes in their valve tissue, where male valvular tissue adopts a calcified phenotype and female tissue becomes more fibrotic. The molecular mechanisms that regulate sex‐specific calcification in valvular tissue remain poorly understood. Here, we explored the role of osteopontin (OPN), a pro‐fibrotic but anti‐calcific bone sialoprotein, in regulating the calcification of female aortic valve tissue. Recognizing that OPN mediates calcification processes, we hypothesized that aortic valvular interstitial cells (VICs) in female tissue have reduced expression of osteogenic markers in the presence of elevated OPN relative to male VICs. Human female valve leaflets displayed reduced and smaller microcalcifications, but increased OPN expression relative to male leaflets. To understand how OPN expression contributes to observed sex dimorphisms in valve tissue, we employed enzymatically degradable hydrogels as a 3D cell culture platform to recapitulate male or female VIC interactions with the extracellular matrix. Using this system, we recapitulated sex differences observed in human tissue, specifically demonstrating that female VICs exposed to calcifying medium have smaller mineral deposits within the hydrogel relative to male VICs. We identified a change in OPN dynamics in female VICs in the presence of calcification stimuli, where OPN deposition localized from the extracellular matrix to perinuclear regions. Additionally, exogenously delivered endothelin‐1 to encapsulated VICs increased OPN gene expression in male cells, which resulted in reduced calcification. Collectively, our results suggest that increased OPN in female valve tissue may play a sex‐specific role in mitigating mineralization during AVS progression.